Impact of wall shear stress and ligand avidity on binding of anti-CD146-coated nanoparticles to murine tumor endothelium under flow - Thomann, Stefan; Baek, Sunhwa; Ryschich, Eduard (OncoTarget, 2015)
The endothelial phenotype of tumor blood vessels differs from the liver and forms an important base for endothelium-specific targeting by antibody-coated nanoparticles. Although differences of shear stress and ligand avidity can modulate the nanoparticle binding to endothelium, these mechanisms are still poorly studied. This study analyzed the binding of antibody-coated nanoparticles to tumor and liver endothelium under controlled flow conditions and verified this binding in tumor models in vivo. Binding of anti-CD146-coated nanoparticles, but not of antibody was significantly reduced under increased wall shear stress and the degree of nanoparticle binding correlated with the avidity of the coating. The intravascular wall shear stress favors nanoparticle binding at the site of higher avidity of endothelial epitope which additionally promotes the selectivity to tumor endothelium. After intravenous application in vivo, pegylated self-coated nanoparticles showed specific binding to tumor endothelium, whereas the nanoparticle binding to the liver endothelium was very low. This study provides a rationale that selective binding of mAb-coated nanoparticles to tumor endothelium is achieved by two factors: higher expression of endothelial epitope and higher nanoparticle shearing from liver endothelium. The combination of endothelial marker targeting and the use of shear stress-controlled nanoparticle capture can be used for selective intratumoral drug delivery.
Gesehen am 30.06.2020